Comparison of cytotoxicity of cigarette smoke extract derived from heat-not-burn and combustion cigarettes in human vascular endothelial cells - Takahiro Horinouchi; Soichi Miwa (Journal of Pharmacological Sciences, 2021)
The present study compared the properties of mainstream smoke generated from heat-not-burn (HNB) cigarettes and a combustion cigarette (hi-lite™ brand). Three types of cigarette heating devices were used to generate cigarette smoke at different heating temperatures [Ploom S™ (200 °C), glo™ (240 °C), and IQOS™ (300–350 °C)]. Mainstream smoke was generated using the following puffing regimen: volume, 55 mL; duration, 3 s; and interval, 30 s. The rank order of particulate phase (nicotine and tar) amounts trapped on a Cambridge filter was Ploom S < glo < IQOS < hi-lite. Heated cigarette-derived smoke extract (hCSE) from the devices except for Ploom S, and burned CSE (bCSE) decreased mitochondrial metabolic activity (glo < IQOS < hi-lite) in human vascular endothelial cells. Furthermore, the cytotoxicity was reduced by removing the particulate phase from the mainstream smoke. Endothelial nitric oxide synthase activity was reduced by nicotine- and tar-free CSE of IQOS and hi-lite (IQOS < hi-lite), but not Ploom S and glo. These inhibitory effects were diminished by removing the carbonyl compounds from the mainstream smoke. These results indicated that the cytotoxicity of hCSE was lower than that of bCSE in vascular endothelial cells.